2016
DOI: 10.1002/chem.201602430
|View full text |Cite
|
Sign up to set email alerts
|

Hydrazones as Singular Reagents in Asymmetric Organocatalysis

Abstract: This Minireview summarizes strategies and developments regarding the use of hydrazones as reagents in asymmetric organocatalysis, their distinct roles in nucleophileelectrophile reactions, cycloadditions and cyclizations. The key structural elements governing the reactivity of these reagents in a preferred pathway will be discussed, as well as their different interactions with organocatalysts, leading to diverse activation modes. Along these studies, the synthetic equivalence of Nmonoalkyl-, N,N-dialkyl-and N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(29 citation statements)
references
References 84 publications
(95 reference statements)
0
26
0
Order By: Relevance
“…Acting as mild carbon π‐nucleophiles, their additions to C=X (X=C, N, O) bonds are useful C−C bond‐forming reactions for the synthesis of enantiomerically pure compounds, including highly functionalized amines and alcohols . The development of asymmetric catalytic versions of these reactions was initially hindered by the sensitivity of these reagents toward most Lewis acidic metal complexes, but the milder nature of organocatalytic activation strategies appeared to solve these compatibility issues . Thus, LUMO‐lowering activation of imines by axially chiral 1,1′‐bi‐2‐naphthol (BINOL), phosphoric acid, or dicarboxylic acid derivatives allowed the 1,2‐addition of N,N‐dialkylhydrazones (DAHs) to yield enantiomerically enriched α‐aminohydrazones (Scheme A) .…”
Section: Introductionmentioning
confidence: 99%
“…Acting as mild carbon π‐nucleophiles, their additions to C=X (X=C, N, O) bonds are useful C−C bond‐forming reactions for the synthesis of enantiomerically pure compounds, including highly functionalized amines and alcohols . The development of asymmetric catalytic versions of these reactions was initially hindered by the sensitivity of these reagents toward most Lewis acidic metal complexes, but the milder nature of organocatalytic activation strategies appeared to solve these compatibility issues . Thus, LUMO‐lowering activation of imines by axially chiral 1,1′‐bi‐2‐naphthol (BINOL), phosphoric acid, or dicarboxylic acid derivatives allowed the 1,2‐addition of N,N‐dialkylhydrazones (DAHs) to yield enantiomerically enriched α‐aminohydrazones (Scheme A) .…”
Section: Introductionmentioning
confidence: 99%
“…6a It was also found that when the original cycloadduct 4a was subjected to the condensation with phenylhydrazine, the originally formed phenylhydrazone 9 underwent intramolecular 1,3-dipolar cycloaddition to give 10 as the final product ( Scheme 3 , bottom). 10 The transformation proved possible to perform in a one-pot fashion without the need to isolate any of the intermediates. Notably, both developed processes proceeded in a diastereoselective manner providing 8 and 10 as single diastereoisomers (for the assignment of relative configuration, see the Supporting Information ).…”
mentioning
confidence: 99%
“…Interestingly, the initially formed product 7 underwent spontaneous intramolecular Diels–Alder cycloaddition to give interesting polycyclic system 8 containing an additional cyclobutane ring . It was also found that when the original cycloadduct 4a was subjected to the condensation with phenylhydrazine, the originally formed phenylhydrazone 9 underwent intramolecular 1,3-dipolar cycloaddition to give 10 as the final product (Scheme , bottom) . The transformation proved possible to perform in a one-pot fashion without the need to isolate any of the intermediates.…”
mentioning
confidence: 99%
“…For example, these compounds have been used extensively in materials science for the synthesis of molecular switches [2], hydrogels [3], sensors, and fluorophores [4]. Other characteristics of the hydrazones are their diverse biomedical applications [5] and their utility as high value synthetic intermediates in asymmetric synthesis [6], synthesis of N-heterocycles [7] and C-H activation [8]. Indeed, these types of scaffolds are key intermediaries in a variety of chemical transformations and can be classified as versatile building blocks for organic synthesis.…”
Section: Introductionmentioning
confidence: 99%